2011
DOI: 10.5194/nhess-11-2483-2011
|View full text |Cite
|
Sign up to set email alerts
|

Using ground based radar interferometry during emergency: the case of the A3 motorway (Calabria Region, Italy) threatened by a landslide

Abstract: Abstract. The rapid assessment of the evolution of the phenomena which occur during an emergency, along with an all weather and h24 monitoring capability, are probably the main characteristics of a system aimed at optimizing intervention in natural disasters, such as landslide collapses. A few techniques are able to provide all these features remotely, hence assuring safe conditions to operators. This paper reports on an application of the GB-InSAR (Ground-Based Interferometric Synthetic Aperture Radar) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…They are transportable and only require from a few tens of minutes to a few hours to be installed (depending on the logistics of the site). Moreover, they can detect "near-real-time" area displacements, without accessing the unstable area, 24 h a day and in all weather conditions (Del Ventisette et al, 2011;Luzi, 2010;Monserrat et al, 2014). On the other hand, some limitations reduce the GBInSAR technique applicability: first of all, the scenario must present specific characteristics in order to reflect microwave radiations, maintaining high coherence values (Luzi, 2010;Monserrat et al, 2014); only a component of the real displacement vector can be identified (i.e., the component parallel to the sensor's line of sight); and maximum detectable velocities are connected to the time that the system needs to obtain two subsequent acquisitions.…”
Section: Gb-insarmentioning
confidence: 99%
“…They are transportable and only require from a few tens of minutes to a few hours to be installed (depending on the logistics of the site). Moreover, they can detect "near-real-time" area displacements, without accessing the unstable area, 24 h a day and in all weather conditions (Del Ventisette et al, 2011;Luzi, 2010;Monserrat et al, 2014). On the other hand, some limitations reduce the GBInSAR technique applicability: first of all, the scenario must present specific characteristics in order to reflect microwave radiations, maintaining high coherence values (Luzi, 2010;Monserrat et al, 2014); only a component of the real displacement vector can be identified (i.e., the component parallel to the sensor's line of sight); and maximum detectable velocities are connected to the time that the system needs to obtain two subsequent acquisitions.…”
Section: Gb-insarmentioning
confidence: 99%
“…DSGSDs (Deep Seated Gravitational Slope Deformations) are defined by Agliardi et al (2001) as slope movements occurring on high relief slopes and with relatively small displacements before the final phase of collapse. GB-InSAR (Ground-Based Interferometric Synthetic Aperture Radar) is an advanced remote sensing monitoring apparatus recently used in landslide EWSs (Del Ventisette et al, 2011;Intrieri et al, 2012). short questions posed to the end-user about the type of landslide and qualitative estimates of the budget available (Fig. 2), as well as questions about the elements at risk and risk scenarios (Fig.…”
Section: Guidelinesmentioning
confidence: 99%
“…Furthermore, in recent years the GB-InSAR technique has developed to an extent where it can significantly contribute to the management of major technical and environmental disasters (Del Ventisette et al, 2011;Broussolle et al, 2014;Lombardi et al, 2017;Bardi et al, 2017a, b). Between 31 October 2010 and 2 November 2010 the whole Veneto region (north-eastern Italy; Fig.…”
Section: Introductionmentioning
confidence: 99%